Congenital Complete Atrioventricular Heart Block in a Pregnant Woman with Sjögren Syndrome: Prenatal Care Follow-Up and the Challenge of Intrauterine Treatment - Milene Carvalho Carrilho; Nathalie Jeanne Bravo-Valenzuela; Edward Araujo Júnior
Abstract The present report describes a case of complete atrioventricular block (CAVB) diagnosed at 25 weeks of gestation in a pregnant woman with Sjögren's syndrome and positive anti-Ro/SSA antibodies. Fluorinated steroids (dexamethasone and betamethasone) and terbuline were used to increase the fetal heart rate, but the fetal heart block was not reversible, and the administration of drugs was discontinued due to maternal collateral effects. Follow-up fetal echocardiograms were performed, and the fetus evolved with pericardial effusion, presence of fibroelastosis in the right ventricle, and ventricular dysfunction. Interruption of pregnancy by cesarean section was indicated at 34 weeks of gestation, and a cardiac pacemaker was implanted in the male newborn immediately after birth. Therapy for fetuses with CAVB is controversial mainly regarding the use or not of corticosteroids; however, monitoring of the atrioventricular interval by fetal echocardiography should be performed in fetuses from pregnant women with positive autoantibodies anti-Ro/SSA and/or anti-La/SSB to prevent the progression to CAVB.